Meningkatkan Hasil Belajar Bahasa Inggris pada Ketrampilan Speaking Materi Descriptive Lisan Sederhana yang Berterima Melalui Model PBL - Tri Rahayu Budi Astuti; Arin Arianti; Atika Hernian Asri (Journal on Education, 2023)
The aim of this research is to determine whether the use of Problem-Based Learning (PBL) can enhance English learning outcomes in the skill of speaking with simple descriptive oral material in an acceptable manner. The research method employed is classroom action research, consisting of 2 cycles. The research subjects are 32 students from class VII F at SMPN2 Jogonalan in the academic year 2023/2024. Data analysis utilizes comparative descriptive analysis techniques by comparing the initial conditions with the results achieved in each cycle. Additionally, qualitative descriptive analysis is used to analyze observation results by comparing observations and reflections in cycles 1 and 2. Based on the discussion of the data analysis presented, it is evident that the PBL model has been able to improve English learning outcomes in the skill of speaking with simple descriptive oral material in a satisfactory manner. The PBL learning model provided to students in class VII F has been successfully completed satisfactorily. The initial completion rate was only 60%. However, after implementing the PBL model, the completion rate increased to 86%, with a minimum passing grade of 7.4. Conclusively, based on the research findings, it can be inferred that the PBL model can enhance English learning outcomes in the skill of speaking with acceptable descriptive oral material for students in class VII F at SMPN2 Jogonalan in the first semester of the academic year 2023/2024. It is recommended for teachers to enhance the learning outcomes in speaking skills with simple descriptive oral material using the PBL teaching model.